Deep learning the collisional cross sections of the peptide universe from a million experimental values - Florian Meier (Nature Portfolio, 2021)
Proteomics has been advanced by algorithms that can predict different peptide features, but predicting peptide collisional cross sections (CCS) has remained challenging. Here, the authors measure over one million CCS values of tryptic peptides and develop a deep learning model for peptide CCS prediction.